Weed Seed Species Inventory of Wheat Imported through Tanjung Perak Port - Ulya Wildaniyah; Rahma Susila Handayani (Jurnal Perlindungan Tanaman Indonesia, 2020)
Wheat seeds importation has the potential of weed seeds that can harm Indonesia's biodiversity. This study aims to determine the types and morphological characters of weed seeds carried by imported wheat from Australia, Canada, and Ukraine through the port of Tanjung Perak-Surabaya for January-June 2018. The research was started by collecting weed seeds from wheat samples, observing using a SMZ 1270 stereo microscope and identifying them using a reference book. The weed seeds were successfully identified as 13 families with 20 species originating from Australia, Canada and Ukraine. The most common types of weeds are from the Poaceae family. Weed this family are often found in the form of florets, the seeds of which are called caryopsis are coated in lema and palea, as in grains. Weed seed species found in wheat commodities from the three countries, are: Avena fatua, Brassica campestris, and Polygonum convolvulus, are not classified as quarantine pest.